Igor Burkhanov. Linguistic Foundations of Ideography: Semantic Analysis and Ideographic Dictionaries - Hüllen, Werner (Lexikos, 2002)
In his book, Igor Burkhanov assumes that cognitive semantics, as developed mainly in the United States of America from about 1980, is a linguistic innovation which lends itself to a thorough renovation of pedagogical dictionaries. In order to show this convincingly, he discusses lexicography as an applied discipline of linguistics with the study of meaning at its centre. The various types of ideographical (onomasiological) dictionaries extant are presented and the development of semantics is unravelled from the field theory of the early 20th century to the present. After a general sketch of the learner’s ideographical dictionary, the possible contribution of cognitive semantics is shown in a number of sample entries. The book is evaluated as being highly informative and equally highly honest, because the many shortcomings and deficiencies of pedagogical metalexicography are pointed out. A careful weighing of its statements gives occasion for some critical ideas about the relationship between linguistics and philology, the terminology and typology of ideographical dictionaries, and the feasibility of the proposed new dictionaries for didactic purposes.